Insights into the control of taxane metabolism: Molecular, cellular, and metabolic changes induced by elicitation in Taxus baccata cell suspensions - Perez-Matas, Edgar; Hanano, Abdulsamie; Moyano, Elisabeth; Bonfill, Mercedes; Cusido, Rosa M.; Palazon, Javier (Frontiers in Plant Science, 2022)
More knowledge is needed about the molecular/cellular control of paclitaxel (PTX) production in Taxus spp. cell cultures. In this study, the yield of this anticancer agent in Taxus baccata cell suspensions was improved 11-fold after elicitation with coronatine (COR) compared to the untreated cells, and 18-fold when co-supplemented with methyl-β-cyclodextrins (β-CDs). In the dual treatment, the release of taxanes from the producer cells was greatly enhanced, with 81.6% of the total taxane content being found in the medium at the end of the experiment. The experimental conditions that caused the highest PTX production also induced its maximum excretion, and increased the expression of taxane biosynthetic genes, especially the flux-limiting BAPT and DBTNBT. The application of COR, which activates PTX biosynthesis, together with β - CDs, which form inclusion complexes with PTX and related taxanes, is evidently an efficient strategy for enhancing PTX production and release to the culture medium. Due to the recently described role of lipid droplets (LDs) in the trafficking and accumulation of hydrophobic taxanes in Taxus spp. cell cultures, the structure, number and taxane storage capacity of these organelles was also studied. In elicited cultures, the number of LDs increased and they mainly accumulated taxanes with a side chain, especially PTX. Thus, PTX constituted up to 50-70% of the total taxanes found in LDs throughout the experiment in the COR + β - CD-treated cultures. These results confirm that LDs can store taxanes and distribute them inside and outside cells.